Effect of Surfactants on Total Phenol Content from Sonication Extraction of Moringa (Moringa oleifera Lamk) Leaves in Vegetable Oil - Azhar, Istighfarin Meilidya; Mahmudah, Rif'atul; Fasya, Ahmad Ghanaim (Walisongo Journal of Chemistry, 2024)
This research aimed to determine the effect of variations in surfactant addition and sonication extraction time on the total phenolic content of Moringa leaves in vegetable oils, namely Virgin Coconut Oil (VCO) and Extra Virgin Olive Oil (EVOO). Moringa leaf extract in VCO and EVOO at varying volume additions of tween 80 of 0 mL; 0.1 mL; 0.2 mL; 0.3 mL; and 0.4 mL, as well as variations in extraction time, namely 0, 10, 20, and 30 minutes. The solution mixture was sonicated at room temperature with a frequency of 42 kHz. The extraction results were tested for total phenol content using the total phenol measurement method (Folin-Ciocalteu), whose absorption was measured using a UV-Vis Spectrophotometer. The best variation was the addition of tween 80 volume of 0.4 mL and extraction time of 30 minutes; sonicated Moringa leaf extract in VCO was 39.28 ± 1.75 mg GAE/g and EVOO was 57.80 ± 2.89 mg GAE/g. Furthermore, the typical functional groups of phenolic compounds in the best Moringa leaf herbal oil extract in VCO and EVOO were identified using an FTIR spectrophotometer.